Extension of Authority to Confer Bachelor of Education Degrees in Alberta - Bischoff, Dale P. (Alberta Journal of Educational Research, 2001)
This retrospective policy study identified how and why authority to confer Bachelor of Education degrees was extended to private colleges in Alberta. Data collection consisted of document review and interviews with key actors who played important roles in the adoption of the policy change. The study had two foci: the process by which the King's University College in Edmonton was able to attain authority to confer BEd degrees, and on postsecondary policy change in Alberta using Sabatier and Jenkins-Smith's (1993, 1997) Advocacy Coalition Framework (ACE). Two sources of the policy change were identified: local political pressures and international pressures for neoliberalization of public policy. The study confirmed the utility of the ACE to represent and explain the case study information on extension of authority to confer BEd degrees in Alberta. A significant finding was the intractability of the policy change due to opposition by a consensus of professional educators. Although educator elites anticipated additional extension of authority to confer BEd degrees and increasing privatization of the postsecondary education system, respondents opposing the policy change anticipated continuing resistance from educational stakeholders. This potential conflict has implications for teacher preparation, the practice of school administrators, and for education generally. Differentiation in teacher preparation that may result from a proliferation of BEd programs has quality control implications for the Teacher Certification Branch of the Department of Alberta Education and the Private Colleges Accreditation Board of Alberta.